Land Management for Agriculture After The 2010 Merapi Eruption - Utami, Sri Nuryani Hidayah; Purwanto, Benito Heru; Marwasta, Djaka (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2018)
The great eruptions of Mount Merapi in 2010 have drawn a great deal of attention from both national and international media.The month-long eruptions killed more than 200 people, displaced over 100,000 residents, killed over 1,000 livestock and destroyed over 1,000 hectares of productive farming fields. Incidentally, agriculture is one of the livelihood sectors that suffered heavily. Further, it impacted farmers the most as they depend on farming activities as their main source of livelihood. After, the eruption, land management became based on material type and condition of the land.. Principles of land management involve the provision of appropriate environmental needs of plants, the availability of moisture, nutrients, colloidal holding nutrients, and aeration. In short, they entail the technical aspects of recovery after the eruption of plants based on the conditions of the land. Also included are crop diversification (intercropping cultivation, crops rotation, mixed farming, etc) and intensification of yard (horticulture crops, hedge rows); as well as reinforcing of core and source of cattle nutrition, for example gliricedea; fast growing and producing crops are needed but those that need high capital / major costs for planting and care are not required. Furthermore, the concept of post-eruption land arrangements needs to be formulated based on the configuration of the land which is mainly related to local circumstances such as topography, hydrology, meteorology, and natural drainage systems.